Strategic analysis for TM Consumer sales Sarawak / Ariati Suradi ... [et al.] - Suradi, Ariati; Wan Ali, Sharifah Khadijah; Peter, Theresa Korina (2009)
The objective of this Applied Business Project is to conduct a strategic analysis of Consumer Sales Sarawak (CSS), a business unit in TM responsible to market telecommunication products on the fixed line category in Sarawak. This study also aims to analyze CSS's sales performance and to provide recommendations on ways to enhance its marketing strategy in line with the current level of financial performance. In carrying out the strategic analysis of CSS, an internal audit will be performed in the three areas relevant to CSS, which are management, marketing and financial. SWOT Analysis will be used to conclude our findings and in identifying the strengths, weaknesses, opportunities and threats of CSS.